Impact of Positive Charges in a Fringing Field Bio-Tunnel-FET Device with Source Underlap - Macambira, Christian N.; Agopian, Paula G. D. [UNESP]; Martino, Joao A.; IEEE (Ieee, 2021)
In this paper, the sensitivity of the fringing field ntype tunneling field-effect transistor biosensor (Bio-nTFET) was investigated over the influence of positive fixed charges density (QBio) and dielectric constant k, in the source underlap (LUS) region. Numerical simulations were performed using Sentaurus TCAD device simulator. The presence of different biomolecules, in the LUS region, affects the drain current of the on-state (IOn). It is shown that the sensitivity of the Bio-nTFET increases 3 orders of magnitude from k = 1 to k = 10 due to the improved fringing field that reduces the tunneling length resulting in a higher tunneling current. The sensibility also increases for a higher values of QBio. The highest sensitivity value obtained in this work was 6.103 A/A for Q(Bio) = 1.10(12) cm(-2) and k = 10. The proposed device shows great potential as a biosensor based on TFET devices.
Keywords: Biosensor; Bio-TFET; Fringing Field; Source Underlap; Sensitivity; Permittivity